Detection of Mycobacterium leprae using real-time PCR in paucibacillary leprosy patients with negative acid-fast bacilli smears (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Leprosy is an infectious disease that is still a health problem worldwide, including in Indonesia. The clinical symptoms are similar to other skin diseases and it is difficult to establish a diagnosis for paucibacillary (PB) leprosy. Current serological and histopathological tests have limitations, especially in patients with negative acid-fast bacilli (AFB). Serological tests often give false-negative results, while histopathological results often consist of non-specific inflammation. Probe-based real-time polymerase chain reaction (RT-PCR) assays is an alternative test that may be more sensitive and more specific to detect Mycobacterium leprae. METHODS This study was done in June 2015 until March 2016; detected M. leprae in PB patients with negative AFB smears using TaqMan® probe-based RT-PCR assay on slit skin scrapings and skin biopsy specimens from 24 patients. The skin scrapings were obtained from skin tissue on ear lobes, skin lesions, as well as those from biopsy. Samples were tested with RT-PCR while histopathological examinations were only performed on skin from biopsy. RESULTS The RT-PCR assay showed positive results of 21%, 25%, and 96% for specimens obtained from skin scrapings of the ear lobe, skin lesions, and skin biopsy, respectively. On the other hand, the positive rate for the histopathological test from skin biopsy was 79%. It indicated that the TaqMan® RT-PCR assay could increase the diagnostic capacity of histopathological examination by as much as 17%. CONCLUSIONS TaqMan® PCR assay can improve the diagnostic capacity of histopathological examinations, which could be used as the new gold standard for the diagnosis of leprosy.